Spiritual Emotional Freedom Technique (SEFT) Reduces Breathing Frequency in Bronchial Asthma - Sholichin, Sholichin; Fittarsih, Niya; Syahrun, Syahrun; Khumaidi, Khumaidi; Metungku, Fanny; Sari, Rita Puspa (Fakultas Kedokteran, 2024)
Introduction: Asthma is a chronic inflammatory disease of the airways that causes intermittent and reversible airflow disturbances resulting in hyperactivity of the bronchi to various stimuli characterized by recurrent episodic symptoms in the form of wheezing), coughing, a feeling of heaviness in the chest and shortness of breath. Shortness of breath is characterized by increasing respiratory frequency. The main nursing intervention for the problem of shortness of breath is airway management and monitoring respiratory frequency by ensuring lung function is as normal as possible and maintaining it and preventing airway obstruction, one of which is by carrying out SEFT. The aim of this study was to analyze the difference in the decrease in respiratory frequency before and after SEFT. Method: This research is a quasi-experimental research with a randomized one group pretest-posttest design approach. Sampling was carried out using simple random sampling based on inclusion criteria. Data analysis used the alternative Wilcoxon test with α 0.05. The total research sample was 100 respondents using random sampling techniques. Results: There were 94 respondents whose respiratory frequency value after SEFT was smaller than the respiratory frequency before SEFT, 2 respondents whose respiratory frequency value after SEFT was greater than the respiratory frequency value before SEFT and 4 respondents whose values were the same before and after SEFT. The statistical test results showed that p < (0.05), meaning there was a significant difference in respiratory frequency before and after SEFT was carried out. Conclusion: this research shows that SEFT can reduce respiratory frequency. This research recommends that SEFT can be an intervention in nursing care for asthma patients.Keywords: SEFT, Respiratory Frequency, Asthma.